Bringing "honest capital" to poor borrowers: The passage of the uniform small loan law, 1907-1930 - Bruce G. Carruthers; Timothy Guinnane; Yoonseok Lee (Yale University, Economic Growth Center, 2009)
The Uniform Small Loan Law (USLL) was the Russell Sage Foundation's primary device for fighting what it viewed as the scourge of high-rate lending to poor people in the first half of the twentieth century. The USLL created a new class of lenders who could make small loans at interest rates exceeding those allowed for banks under the normal usury laws. About two-thirds of the states had passed the USLL by 1930. This paper describes the USLL and then uses econometric models to investigate the state characteristics that influenced the law's passage. We find that urbanization and state-level economic characteristics played significant roles. So did measures of the state's banking system. We find no evidence that party-political affiliations had any effect, which is consistent with the USLL's progressive” character. Finally, we find little evidence that the passage of the USLL in one state made passage more likely in neighboring or similar states. If anything, the cross-state influences were negative. Our findings suggest that the Russell Sage Foundation only imperfectly understood the political economy of the USLL, and that a different overall approach might have produced a result closer to their aims.
Keywords: N21; N22; I38; G21; G28; K23; 330; uniform law; small loans; consumer credit; usury laws